Gambaran Kompetensi Profesional Instruktur Menurut Warga Belajar dalam Pembelajaran Matematika di Bimbel Eye Level Kota Padang - Rahmi Fauziah; Wirdatul Aini; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by Mathematics learning learning activities that went well. It can be seen from the high learning outcomes of learning citizens. The purpose of this study is to describe professional competencies including (1) mastering the concepts and mindset of science that underlie the subject matter, (2) developing learning material, (3) developing professionalism in a sustainable manner, (4) utilizing information and communication technology to develop themselves. This type of research is quantitative descriptive. The population in the study amounted to twenty and samples of fifteen people. The sampling technique in this research is random sampling method. Data collection techniques and tools used are interviews and interview guidelines. Data analysis techniques use a percentage formula. The findings of this study indicate that the professional competence of instructors according to learning citizens in the teaching and learning process of Mathematics is very good, it includes the following four aspects: (1) mastering the concepts and scientific mindset that underlie the subject matter, (2) developing the subject matter, (3) develop professionalism in a sustainable manner, (4) utilize information and communication technology to develop themselves.It is recommended for instructors to keep maintaining and improving professional competencies that are already good in the future.